2007
DOI: 10.1002/ls.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal‐free phosphorus anti‐wear compounds on passenger car emissions and fuel economy

Abstract: There has been concern for many years that phosphorus (P) from engine oils is volatilised, passes through the combustion chamber and is deposited on the catalyst system in passenger cars, causing the emission control system to lose efficiency. Therefore, as new engine oil specifications have been introduced, there has been a trend to require a reduction in P in fresh engine oils. The primary P source in current engine oils is zinc dithiophosphate (ZDP), which acts as an anti‐wear agent and antioxidant. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…6 Alkyl phosphates, such as tri(n-butyl)phosphate (TNBP), are already used as additives in gear lubricants and industrial lubricants. 7 Moreover, aryl phosphates, such as tri(m-cresyl) phosphate (TCP), are included in most aviation lubricant formulations. 8 Both TNBP and TCP have also been used as vapour phase lubricants (VPLs) for tribological systems that operate at very high temperature (> 700 K).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Alkyl phosphates, such as tri(n-butyl)phosphate (TNBP), are already used as additives in gear lubricants and industrial lubricants. 7 Moreover, aryl phosphates, such as tri(m-cresyl) phosphate (TCP), are included in most aviation lubricant formulations. 8 Both TNBP and TCP have also been used as vapour phase lubricants (VPLs) for tribological systems that operate at very high temperature (> 700 K).…”
Section: Introductionmentioning
confidence: 99%
“…Some promising examples include phosphate esters and thiophosphate esters . Alkyl phosphates, such as tri- n -butyl phosphate (TNBP), are already used as additives in gear lubricants and industrial lubricants . Moreover, aryl phosphates, such as tri- m -cresyl phosphate (TCP), are included in most aviation lubricant formulations .…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0036-8792.htm content of ZDDP additives in lubricants, as well as a mixture of solutions based on ZDDP, have been investigated regarding their action to form protective films (Devlin et al, 2008;Spikes, 2008;Rastogi, et al, 2013). Neville and Morina studied the friction coefficient behaviour by replacing base oil (PAO6), ZDDP and molybdenum dialkyldithiocarbamate with a combination of these lubricants along a tribotest (Morina and Neville, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attempts to replace ZnDTP by other additives have been carried out from the viewpoint of restrictions on lubricant phosphorus and sulphur content in engine oils, caused by concern for exhaust catalyst poisoning. Devlin et al [15] examined alkyl phosphate (sulphur-free) type antiwear additive in catalyst emission and fuel economy tests, and found that the performance improved when alkyl phosphates were used in the place of ZnDTPs. Katafuchi and Shimizu [16] found that several synthesized compounds having an ester group near the sulphur atom in the molecule achieved an excellent antiwear performance, equivalent to ZnDTP.…”
Section: Introductionmentioning
confidence: 99%